Comparative study on the libido, semen quality and fertility of Brahman cross, Holstein Friesian cross and Red Chittagong breeding bulls: Libido, semen quality and fertility of breeding bulls (Bangladesh Journal of Animal Science, 2018)
The present study was undertaken to compare the performance of 8 (eight) breeding bulls of three different genetic groups such as Brahman × local (4 bulls), Holstein Friesian × local (2 bulls) and Red Chittagong (2 bulls) based on libido, semen quality and fertility. Semen parameters were evaluated from 30 ejaculates from each bull and fertility rate was calculated based on 60-days non-return rate via AI using these semen samples. Genetic group of breeding bulls had significant (p